COST-EFFECTIVENESS ANALYSIS USE OF ANTIBIOTICS IN COVID-19 PATIENTS - Mera Putri Pratitis; Yulia Pratiwi; Wildayanti Wildayanti; Cita Nuryatunnisa (Cendekia Journal of Pharmacy, 2023)
Corona Virus Disease 2019 (COVID-19) is an infectious disease caused by severe acute respiratory syndrome coronavirus 2 (SAR-CoV-2) and can cause respiratory tract infections. This disease requires a large cost in the management process. This has an impact on the economic condition of the patient, so it is necessary to identify pharmacoeconomic studies. One of the pharmacoeconomic methods that can be used is Cost-Effectiveness Analysis, this method is used to select and calculate the best therapeutic costs and benefits (outcomes) for several therapeutic options for the same purpose. This study aims to analyze the cost-effectiveness of using the antibiotics azithromycin and levofloxacin in the treatment of COVID-19 at the Fastabiq Sehat General Hospital, PKU Muhammadiyah Pati. Sampling in this study was carried out by purposive sampling. Samples obtained according to the inclusion criteria were 57 patients. The data was taken from the patient's medical records, pharmaceutical installations, and finances including characteristics, drug use data, and data on total medical costs. Costs are reviewed from direct medical costs (direct medical costs). The effectiveness of therapy for COVID-19 patients at Fastabiq Sehat General Hospital PKU Muhammadiyah Pati reached the target in the antibiotic azithromycin group with a percentage (80.76%). The ACER value showed the antibiotic azithromycin was Rp.97,809 and levofloxacin was Rp. 127,285. The therapy model that can be used as a standard treatment for COVID-19 is azithromycin at the RSU Fastabiq Sehat, PKU Muhammadiyah Pati.